Use of yoga in outpatient eating disorder treatment: a pilot study. Issue 1 (December 2016) - Hall, Allison; Ofei-Tenkorang, Nana; Machan, Jason; Gordon, Catherine
Abstract Background Individuals with restrictive eating disorders present with co-morbid psychiatric disorders and many attempt to control symptoms using strenuous exercises that increase caloric expenditure. Yoga offers a safe avenue for the engagement in physical activity while providing an outlet for disease-associated symptoms. This study sought to examine use of yoga practice in an outpatient setting and its impact on anxiety, depression and body image disturbance in adolescents with eating disorders. Methods Twenty adolescent girls were recruited from an urban eating disorders clinic who participated in weekly yoga classes at a local studio, in addition to standard multidisciplinary care. Yoga instructors underwent training regarding this patient population. Participants completed questionnaires focused on anxiety, depression and body image disturbance prior to the first class, and following completion of 6 and 12 classes. Results In participants who completed the study, a statistically significant decrease in anxiety, depression, and body image disturbance was seen, including: Spielberger State anxiety mean scores decreased after the completion of 7–12 yoga classes [47 (95%CI 42–52) to 42 (95%CI 37–47), adj.p  = 0.0316]; as did the anorexia nervosa scale [10 (95% CI 7–12) vs. 6 (95%CI 4–8), adj.p  = .0004], scores on Beck depression scales [18 (95%CI 15–22) to 10 (95%CI 6–14), adj.p  = .0001], and weight and shape concern scores [16 (95%CI 12–20) to 12 (95%CI 8–16), adj.p  =0.0120] and [31 (95%CI 25–37) to 20 (95%CI 13–27), adj.p  = 0.0034], respectively. No significant changes in body mass index were seen throughout the trial. Conclusions Yoga practice combined with outpatient eating disorder treatment were shown to decrease anxiety, depression, and body image disturbance without negatively impacting weight. These preliminary results suggest yoga to be a promising adjunct treatment strategy, along with standard multidisciplinary care. However, whether yoga should be endorsed as a standard component of outpatient eating disorder treatment merits further study.